MENINGKATKAN KEAKTIFAN BELAJAR MATEMATIS SISWA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS-GAMES-TOURNAMENT - Syakilah Caca; Heni Pujiastuti (Jurnal Karya Pendidikan Matematika, 2020)
This research were aimed to describe student activeness in math's geometry curved side using classroom action research and with Teams Games Tournament Subject model. Placed in IX H grade SMP Negeri 1 Ciruas. Data association instrument is using Crossword Puzzle and student activness quotioner. This action research has some steps: pre-Cycle, Cycle I and Cycle II based on the result of this research, may concluded students activeness were enhanced in math this action research, 90% students agreed that using Teams Games Tournament learning model, with help of crossword puzzle was very exciting and helping students in order of understanding topic. Based on the result, may concluded that applying Teams Games Tournament learning model could enhance student activeness in learning maths.